Answer:
[tex]=5r^2-17r+5[/tex]
Step-by-step explanation:
[tex]\mathrm{Apply\:rule}:\quad \left(a\right)=a[/tex]
[tex]\left(8r^2-12r+4\right)=8r^2-12r+4[/tex]
[tex]=8r^2-12r+4-\left(3r^2+5r-1\right)[/tex]
[tex]\mathrm{Apply\:the\:distributive\:law}:\quad \:-\left(a+b\right)=-a-b[/tex]
[tex]-\left(3r^2+5r-1\right)=-3r^2-5r+1[/tex]
[tex]=8r^2-12r+4-3r^2-5r+1[/tex]
[tex]\mathrm{Group\:like\:terms}[/tex]
[tex]=8r^2-3r^2-12r-5r+4+1[/tex]
[tex]\mathrm{Add\:the\:numbers:}\:4+1=5[/tex]
[tex]=8r^2-3r^2-12r-5r+5[/tex]
[tex]\mathrm{Add\:similar\:elements:}\:8r^2-3r^2=5r^2[/tex]
[tex]=5r^2-12r-5r+5[/tex]
[tex]\mathrm{Add\:similar\:elements:}\:-12r-5r=-17r[/tex]
[tex]=5r^2-17r+5[/tex]